Science and mission status of EUSO-SPB2 - Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; Ave Pernas, M.; et al. (Proceedings of Science, 2022)
The Extreme Universe Space Observatory on a Super Pressure Balloon II (EUSO-SPB2) is a second generation stratospheric balloon instrument for the detection of Ultra High Energy Cosmic Rays (UHECRs, E > 1 EeV) via the fluorescence technique and of Very High Energy (VHE, E > 10 PeV) neutrinos via Cherenkov emission. EUSO-SPB2 is a pathfinder mission for instruments like the proposed Probe Of Extreme Multi-Messenger Astrophysics (POEMMA). The purpose of such a space-based observatory is to measure UHECRs and UHE neutrinos with high statistics and uniform exposure. EUSO-SPB2 is designed with two Schmidt telescopes, each optimized for their respective observational goals. The Fluorescence Telescope looks at the nadir to measure the fluorescence emission from UHECR-induced extensive air shower (EAS), while the Cherenkov Telescope is optimized for fast signals (∼10 ns) and points near the Earth's limb. This allows for the measurement of Cherenkov light from EAS caused by Earth skimming VHE neutrinos if pointed slightly below the limb or from UHECRs if observing slightly above. The expected launch date of EUSO-SPB2 is Spring 2023 from Wanaka, NZ with target duration of up to 100 days. Such a flight would provide thousands of VHECR Cherenkov signals in addition to tens of UHECR fluorescence tracks. Neither of these kinds of events have been observed from either orbital or suborbital altitudes before, making EUSO-SPB2 crucial to move forward towards a space-based instrument. It will also enhance the understanding of potential background signals for both detection techniques. This contribution will provide a short overview of the detector and the current status of the mission as well as its scientific goals.
CRIS-Team Scopus Importer:2024-12-16